PEMETAAN KERAWANAN TANAH LONGSOR PADA OBJEK WISATA SWAFOTO DI DESA WANAGIRI, KECAMATAN SUKASADA, KABUPATEN BULELENG - Meris Otniel Stefanus Tamonob; Dewa Made Atmaja; Wayan Damar Windu Kurniawan (Pranatacara Bhumandala: Jurnal Riset Planologi, 2021)
Landslides are one of the world's disasters. areas that are prone to landslides when viewed from the topography are mountains and hills with moderate to steep slopes. slope stability is affected due to earthquakes and human activities. This research aims to determine the level of vulnerability and distribution of landslide-prone areas on a selfie photo tourism object in the wanagiri village, Sukasada sub-district and find out the potential loss in landslide-prone areas on a selfie photo tourism object in Wanagiri village, Sukasada sub-district. the process of identifying vulnerability of landslide areas is carried out by scoring each class which has different weights and previously it had been classified in advance according to each class trought overlay analysis on maps that have been classified to get results in the form of landslide vulnerability maps, then to determine the level of landslide vulnerability in tourist attractions then by using an overlay analysis between the landslide vulnerability map and the self-spreading tourism site. the results of this research are vulnerability of landslide maps on selfie photos tourism object which are overlays of slope maps, rainfall maps, land types maps, land use maps and elevation maps (evalation). division point of landslide vulnerability in this research is divided into 5 parts, namely not prone, somewhat vulnerable, quite vulnerable, vulnerable and landslide vulnerability. the results of this research indicate that the tourism objects that are at the level of prone as many as 4 objects, namely hidden hill, selfie tourism spotspot Pak oles, pucak swing and wanagiri tower garden. tourism object with a very vulnerable level is in 1 object, namely the black bamboo tower tourism selfie spot.